Insertion of a movable genetic element, 297, into the T-A-T-A box for the H3 histone gene in Drosophila melanogaster. - Ikenaga, H (1982)
From a cloned library of Drosophila DNA, a recombinant phage was isolated which contained a nucleotide sequence homologous to both the histone gene and a movable genetic element, 297 [Saigo, K., Millstein, L. & Thomas, C.A., Jr. (1981) Cold Spring Harbor Symp. Quant. Biol. 45, 815-827]. We have determined the nucleotide sequences of the termini of 297 as well as its insertion site in the histone gene in the clone. Our results strongly suggest that (i) although 297 ends with typical long terminal repeats, integrated 297 is not bounded by 5' T-G...C-A 3', dinucleotides commonly found at the very ends of integrated forms of other similar genetic elements, and (ii) the insertion of 297 occurred exactly within the T-A-T-A box for the H3 histone gene containing T-A-T-A-T-A. The structures of the insertion sites of 297 were also examined by using two other recombinant clones of the histone gene. A 6-base-pair-long segment, T-A-T-A-T-A, was again found to be present at the insertion sites of 297 in both clones. Based on these results, it was concluded that, at least within the histone gene cluster, the insertion of 297 was carried out in a site-specific fashion with T-A-T-A-T-A as the target sequence.